Comparison of the Suitability of 2 Years Change in Waist Circumference and Body Mass Index in Predicting Hypertension Risk: A Prospective Study in Chinese-Han. - Wenshu Luo; Fengmei Chen; Zhirong Guo; Ming Wu; Chao Hao; Zhengyuan Zhou; Xingjuan Yao (Tehran University of Medical Sciences, 2014)
Currently, obesity has become a worldwide health problem and yet little is known about the impact of changes in obesity indicator on incident hypertension. The aim of this study was to compare the impact of changes in the WC and BMI on incident hypertension in a cohort population.After a baseline investigation, we conducted the first and the second follow-up assessments for subjects after 2 and 5 years, respectively. The associations between the changes in the WC and BMI (measured as the D-value, i.e., the value at the first follow-up minus the value at baseline) and the hazard ratio (HR) of incident hypertension were analyzed with a multilevel Cox proportional hazards regression model.Among 2778 participants without hypertension, 660 developed hypertension between the first and the second follow-up assessments. When both the BMI and WC D-values were included in the regression model, the WC D-value was a predictor of hypertension incidence in both sexes (OR= 1.03 and P values < 0.05 for men and women), but the BMI D-value was no longer a predictor of hypertension incidence in either sex (OR=1.04 for men and 1.01 for women, both P values >0.05). In both sexes, hypertension risk was higher for subjects whose BMI was modified but WC was categorically increasing than for subjects whose WC and BMI were both modified.Both WC and BMI changes were associated with hypertension, but a change in the WC was a better predictor of the hypertension.